HNF4α isoforms: the fraternal twin master regulators of liver function - Radi, Sarah H.; Vemuri, Kiranmayi; Martinez-Lomeli, Jose; Sladek, Frances M. (Frontiers in Endocrinology, 2023)
In the more than 30 years since the purification and cloning of Hepatocyte Nuclear Factor 4 (HNF4α), considerable insight into its role in liver function has been gleaned from its target genes and mouse experiments. HNF4α plays a key role in lipid and glucose metabolism and intersects with not just diabetes and circadian rhythms but also with liver cancer, although much remains to be elucidated about those interactions. Similarly, while we are beginning to elucidate the role of the isoforms expressed from its two promoters, we know little about the alternatively spliced variants in other portions of the protein and their impact on the 1000-plus HNF4α target genes. This review will address how HNF4α came to be called the master regulator of liver-specific gene expression with a focus on its role in basic metabolism, the contributions of the various isoforms and the intriguing intersection with the circadian clock.